Barriers and Facilitators to the International Implementation of Standardized Outcome Measures in Clinical Cleft Practice. (January 2022) - Apon, Inge; Rogers-Vizena, Carolyn R.; Koudstaal, Maarten J.; Allori, Alexander C.; Peterson, Petra; Versnel, Sarah L.; Ramirez, Jessily P.
Objective: To identify barriers and facilitators to international implementation of a prospective system for standardized outcomes measurement in cleft care. Design: Cleft teams that have implemented the International Consortium for Health Outcomes Measurement Standard Set for cleft care were invited to participate in this 2-part qualitative study: (1) an exploratory survey among clinicians, health information technology professionals, and project coordinators, and (2) semistructured interviews of project leads. Thematic content analysis was performed, with organization of themes according to the dimensions of the reach, effectiveness, adoption, implementation and maintenance (RE-AIM) framework: reach, effectiveness, adoption, implementation, and maintenance. Results: Four cleft teams in Europe and North America participated in this study. Thirteen participants completed exploratory questionnaires and 5 interviewees participated in follow-up interviews. Survey responses and thematic content analysis revealed common facilitators and barriers to implementation at all sites. Teams reach patients either via email or during the clinic visit to capture patient-reported outcomes. Adopting routine data collection is enhanced by aligning priorities at the organizational and cleft team level. Streamlining workflows and developing an efficient data collection platform are necessary early on, followed by pilot testing or stepwise implementation. Regular meetings and financial resources are crucial for implementing, sustaining, analyzing collected data, and providing feedback to health care professionals and patients. Fostering patient-centered care was articulated as a positive outcome, whereas time presented challenges across all RE-AIM dimensions. Conclusions: Identified themes can inform ongoing implementation efforts. Intentionally investing time to lay a sound foundation early on will benefit every phase of implementation and help overcome barriers such as lack of support or motivation.